2018
DOI: 10.1080/1028415x.2018.1443996
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and energy drink use by combat arms soldiers in Afghanistan as a countermeasure for sleep loss and high operational demands

Abstract: Objectives: Combat deployments are characterized by high operational demands with limited opportunities for sleep leading to fatigue and degraded cognitive and operational performance. Caffeine in moderate doses is recognized as an effective intervention for physical and cognitive decrements associated with sleep loss. Methods: This report is based on data collected by two separate, independently conducted surveys administered in Afghanistan in 2011-2012. It assessed caffeine use and sleep disruption among U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
13
2
Order By: Relevance
“…However, this finding does not agree with that of other studies which reported that there is no significant association between marijuana use and anxiety even though regular marijuana use has been found to be associated with anxiety symptoms and disorders [51,52]. Our finding could be attributed to the very few waiters using marijuana in this study possibly to help cope with emotional pain from work-related stressors [43].…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this finding does not agree with that of other studies which reported that there is no significant association between marijuana use and anxiety even though regular marijuana use has been found to be associated with anxiety symptoms and disorders [51,52]. Our finding could be attributed to the very few waiters using marijuana in this study possibly to help cope with emotional pain from work-related stressors [43].…”
Section: Plos Onecontrasting
confidence: 99%
“…demands [43]. Again, our finding that about 20% of the waiters consumed alcohol is lower than that found among hotel employees in a Taiwan surveyed where almost all (90%) consumed some kind of alcoholic drinks with 82�5% using alcohol in the previous month [41].…”
Section: Plos Onecontrasting
confidence: 65%
“…Moreover, Service members often combat sleep deprivation with stimulants such as energy drinks, coffee, or caffeinated gum which are recommended by the DoD as safe and effective for maintaining solider performance when sufficient sleep is not attainable. 94 However, the potential medical risks of caffeine overconsumption and the interacting effects of environmental factors in the deployed setting may have further detrimental or beneficial effects on short-, intermediate-, and long-term outcomes of TBI. 95 Although much of the blast-related TBI research in military populations is focused on injuries incurred during combat, Service members are also at risk of exposure to multiple lowlevel blasts during operational and training activities, such as breacher training.…”
Section: During Injurymentioning
confidence: 99%
“…The relationship between ACEs, sleep and health outcomes is particularly relevant in a military context. Soldiers frequently report patterns of disrupted sleep or sleep deprivation during deployment that appears to persist for months following return from deployment (Pruiksma & Peterson, 2018; McLellan, Riviere, Williams, McGurk & Lierberman, 2018). Disrupted sleep prior to deployment further exacerbates the risk of developing new mental health disorders and, when directly compared, insomnia appears to confer nearly as much risk of developing mental disorders as combat exposure (Germain et al, 2013).…”
Section: Introductionmentioning
confidence: 99%